Programming the metabolic gene expression in zebrafish juveniles (Danio rerio) by supra-physiological glucose level during embryogenesis - Rocha, F. (2013)
Using zebrafish as a model organism, assess the effect of high glucose levels during early embryonic stages as a lifelong moderator of metabolic pathways.